Prostate Cancer Diffusion‐Weighted Magnetic Resonance Imaging: Does the Choice of Diffusion‐Weighting Level Matter? - Maier, Stephan E.; Wallström, Jonas; Langkilde, Fredrik; Johansson, Jens; Kuczera, Stefan; Hugosson, Jonas; Hellström, Mikael (Journal of magnetic resonance imaging, 2022)
Background Diffusion‐weighted magnetic resonance imaging plays an important role in multiparametric assessment of prostate lesions. The derived apparent diffusion coefficient (ADC) could be a useful quantitative biomarker for malignant growth, but lacks acceptance because of low reproducibility. Purpose To investigate the impact of the choice of diffusion‐weighting levels (b‐values) on contrast‐to‐noise ratio and quantitative measures in prostate diffusion‐weighted MRI. Study Type Retrospective and simulation based on published data. Subjects Patient cohort (21 men with Prostate Imaging‐Reporting and Data System (PI‐RADS) version 2 score ≥3) from a single‐center study. Field Strength/Sequence 3 T/diffusion‐weighted imaging with single‐shot echo‐planar imaging. Assessment Both clinical data and simulations based on previously acquired data were used to quantify the influence of b‐value choice in normal peripheral zone (PZ) and PZ tumor lesions. For clinical data, ADC was determined for different combinations of b‐values. Contrast‐to‐noise ratio and quantitative diffusion measures were simulated for a wide range of b‐values. Statistical Tests Tissue ADC and the lesion‐to‐normal tissue ADC ratios of different b‐value combinations were compared with paired two‐tailed Student's t‐tests. A P‐value <0.05 was considered statistically significant. Results Findings about b‐value dependence derived from clinical data and from simulations agreed with each other. Provided measurement was limited to two b‐values, simulation‐derived optimal b‐value choices coincided with PI‐RADSv2 recommendations. For two‐point measurements, ADC decreased by 15% when the maximum b‐value increased from 1000 to 1500 seconds/mm2, but corresponding lesion‐to‐normal tissue ADC ratio showed no significant change (P = 0.86 for acquired data). Simulations with three or more measurement points produced ADCs that declined by only 8% over this range of maximum b‐value. Corresponding ADC ratios declined between 2.6% (three points) and 3.8% (21 points). Simulations also revealed an ADC reduction of about 19% with the shorter echo and diffusion time evaluated. Data Conclusion The comprehensive assessment of b‐value dependence permits better formulation of protocol and analysis recommendations for obtaining reproducible results in prostate cancer diffusion‐weighted MRI. Level of Evidence 4 Technical Efficacy Stage 2